Efektivitas Sacubitril/Valsartan dalam Mencegah Gagal Jantung pada STEMI Pasca Percutaneous Coronary Intervention - Andre, Nobian; Adila, Lana; Rizka, Aulia; Rusdi, Lusiani (UI Scholars Hub, 2023)
Heart failure is a possible complication following ST-elevation myocardial infarction (STEMI) even after revascularization. Neuroendocrine activation in the process of ventricular remodeling can be regulated by angiotensin receptor-neprilysin inhibitor (ARNI) as well as angiotensin-converting enzyme (ACE) inhibitor. The use of ARNI in heart failure with reduced ejection fraction has been found to be superior to ACE inhibitor. The role of ARNI on cardiac function in STEMI has not been established. A clinician treating a patient with STEMI considered giving sacubitril/valsartan to reduce the risk of developing heart failure. Literature search was performed in three electronic databases: PubMed, Embase, and Cochrane. Keywords in the form of text words and MeSH terms were arranged using Boolean operator technique. Critical appraisal of selected articles was carried out according to the guideline from Oxford Centre for Evidence-Based Medicine. Four relevant randomized clinical trials were obtained. There was a reduced risk of heart failure events at 6 months following STEMI who underwent percutaneous coronary intervention (PCI) in the sacubitril/valsartan group compared to ACE inhibitor group, with a relative risk (RR) of 0.35 (95%CI 0.15 – 0.84; p=0.037); RR 0.5 (95%CI 0.31 – 0.82; p=0.004); and number needed to treat (NNT) of 6. Similar results were also found in STEMI patients complicated by cardiogenic shock: RR 0.47 (95%CI 0.24 – 0.94; p=0.044). Sacubitril/valsartan is more effective than ACE inhibitor in reducing the risk of heart failure at 6 months following STEMI post-PCI.